Academic Management in the Development of the Education System of Buntet Astanajapura Islamic Boarding School, Cirebon Regency - Dalil, Dalil (Raudhah Publisher, 2024)
Islamic boarding school education is one of the important pillars in the development of Islamic education in Indonesia. Buntet Islamic Boarding School, located in Astanajapura, Cirebon Regency, has a long history of contribution to Islamic education. However, along with the development of the times, the education system in Islamic boarding schools faces challenges, especially in terms of academic management that is able to support the development of educational quality. This study aims to analyze the role of academic management in the development of the education system at Buntet Islamic Boarding School. The methodology used in this study is a qualitative approach with data collection techniques through in-depth interviews, observations, and document analysis. The main informants consisted of Islamic boarding school leaders, academic managers, and teaching staff. Data were analyzed using thematic analysis techniques to identify important patterns in academic management that affect the education system. The results of the study indicate that effective academic management in Buntet Islamic Boarding School includes curriculum planning integrated with Islamic values, competent human resource management, and continuous monitoring and evaluation. In conclusion, the development of the Islamic boarding school education system can be improved through professional, collaborative, and technology-based academic management to answer the challenges of education in the modern era.